The influence of storage time and pH variation on water sorption by different composite resins - George Mário de Araújo Silva Gusmão; Thiago Vinícius Veras De Queiroz; Guilherme Ferrer Pompeu; Paulo Fonseca Menezes Filho; Cláudio Heliomar Vicente da Silva (Wolters Kluwer Medknow Publications, 2013)
Objective: The objective of this work was to assess the influence of storage time and pH cycling on water sorption by different composite resins. Materials and Methods: Nine resin brands were selected and divided into groups: G1-ROK (SDI), G2-ICE (SDI), G3-GLACIER (SDI), G4-Z350 (3M/ESPE), G5-Z250 (3M/ESPE), G6-TPH 3 (DENTSPLY), G7-ESTHET X (DENTSPLY), G8-SUPRAFILL (SSWHITE), and G9-MASTERFILL (BIODINΒMICS). Ninety specimens, ten per group, were obtained using an aluminum matrix. Specimens measured 10 mm diameter × 2 mm width. The groups were divided into subgroups according to the immersion solution: A - control (n = 05) stored in artificial saliva pH = 7.0 and B-test (n = 05) submitted to seven consecutive days of pH cycling (cariogenic challenger) that consisted of immersion in a pH° = 4.3 solution for 6 h followed by immersion in a pH¹ =7.0 solution for 18 h and stored in artificial saliva pH = 7.0 until the end of the experiment. The specimens were weighed on six occasions: T 0 (after fabrication), T 1 (24 h), T 2 (7 days), T 3 (15 days), T 4 (30 days), T 5 (60 days), and then analyzed. The water sorption was determined by the weight difference between the specimens at the time intervals. Results: The mean weight gain was exactly the same for both the subgroups within group G4. The highest means for the control subgroup were found in groups: G1, G5, G7, G8, and G9. For the pH cycling subgroup, the highest means were found in G2, G3, and G6; however, significant differences between the subgroups compared to the mean-weight gain were found for G1, G5, and G7. Conclusion: The water sorption of composite resins is dependent upon their storage time. The pH cycling created a significant impact on resins G1, G5, and G7. The sorption and solubility of composite resins vary according to their chemical composition.